2006
DOI: 10.1039/b503169a
|View full text |Cite
|
Sign up to set email alerts
|

Charge on the move: how electron-transfer dynamics depend on molecular conformation

Abstract: This tutorial review illustrates the many facets whereby the molecular conformation helps to control the rates of through-bond electron transfer. A brief introduction to Marcus theory is given, highlighting the importance of the coupling element and the super-exchange mechanism, before considering the reasons why the coupling element might depend on the molecular geometry. The methods currently available for determination of both the coupling element and the geometry are reviewed and various examples are given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(164 citation statements)
references
References 49 publications
(100 reference statements)
9
155
0
Order By: Relevance
“…We derived a very specific expression for the conformational dependence of the electronic coupling for OPE bridges. [38] This expression is nearly the same as the one expected from consideration of overlap between two mutually rotating p-orbitals, which has previously been reported for TEET, [43,45] and is given in Equation (11).…”
Section: Discussionsupporting
confidence: 54%
“…We derived a very specific expression for the conformational dependence of the electronic coupling for OPE bridges. [38] This expression is nearly the same as the one expected from consideration of overlap between two mutually rotating p-orbitals, which has previously been reported for TEET, [43,45] and is given in Equation (11).…”
Section: Discussionsupporting
confidence: 54%
“…The orbital overlap of adjacent π systems correlates linearly with the cosine between their planes, and the electron-transfer properties between the two π systems is proportional to cos 2 of their torsion angles. [85][86][87] Thus, in Figure 3, the longest-wavelength onset of each spectrum, which reflects the HOMO-LUMO band gap of the compound under investigation, is plotted against cos 2 Φ. The values of the interplane torsion angles Φ were determined by X-ray structural analysis and are reported elsewhere.…”
Section: Uv Absorption Spectroscopymentioning
confidence: 99%
“…The magnitude of the electronic coupling between the terminal chromophores shows ap recise dependence on the dihedral angle around ab ridging biphenyl group, controlled by selecting the bound cations. [55][56][57] Recently,V enkataraman et al [46] and Wandlowski et al [47][48][49][50][51][52] reported the influence of f on changes in the singlemolecule conductivity in substituted biphenyls or conformationally constrained biphenyls in which the biphenyl rings are connected by a( CH 2 ) n link at the 2-and 2'-positions.O nt wisting of the biphenyl system from coplanar (f= 08)t op erpendicular (f= 908), the conductance decreased by af actor of 30. [48] However,r eports of systematics tudies on the influence of f on the electronic coupling and redox processes of bimetallic complexes [ML n (bridge)ML n ] are still scarce.…”
Section: Introductionmentioning
confidence: 97%